ANALYSIS OF THE IMPACT OF GLOBALISATION ON SELECTED INDICATORS OF FIRM´S ACTIVITIES - Štefko, Róbert; Sojka, Ladislav (European Scientific Journal, ESJ, 2015)
The paper describes the characteristics of globalization, as a typical phenomenon of economic development. It describes the definitions of globalization as well as the positive and negative aspects of globalization. Given the many times contradictory assessment of the impact of globalization, a research was conducted on a sample of 69 Slovak companies which were affected by the globalization process in the last five years. The paper studies the impact of globalization on the performance, remuneration, relations between managers and employees, as well as to work – life balance. The study found a statistically significant positive impact on the performance and remuneration and a negative even though statistically insignificant impact on employee relationships. It was found a strong negative correlation between the degree of globalization and the work – life balance.